Effect of ionic substitution on the structural, dielectric and electrical properties of bismuth zinc niobate ceramics - (:unkn) unknown (KOREAN ASSOC CRYSTAL GROWTH, INC, 2012)
The effects of tin substitution on the structural, dielectric and electrical properties of the Bi1.5Zn0.92Nb1.5O6.92 pyrochlore ceramics have been investigated. Tin atoms was substituted in the A (Bi1.5Zn0.46)-site instead of zinc and in the B ((Zn0.46Nb1.5)-site instead of niobium in accordance to the chemical formulae Bi1.5Zn0.92Nb1.5-xO6.92-x/2 and (Bi1.5-x/3Zn0.46-3x/2Snx)(Nb1.5Zn0.46)O-6.92, for 0.00 <= x <= 0.40 and 0.00 <= x <= 0.60, respectively. A relative single phase formation of the structures was possible for x values less than 0.25 and less than 0.10. Pronounced tunability in the dielectric constant values associated with very low dielectric loss are obtainable by Sn substitution. Furthermore, a frequency invariant but linearly varying temperature dependent dielectric constant is observed. The electrical conductivity decreased by two and one order of magnitude for the A and B-site substitutions, respectively. The temperature-dependent conductivity analysis in the temperature region of 300-500 K, reflected the existence of shallow and deep impurity energy levels being created by the doping process.
Keywords: Mixing; Composites; X-ray methods; Electrical properties; Dielectric properties; BI1.5ZN0.92NB1.5O6.92; BEHAVIOR; ENERGY